1985
DOI: 10.1002/eji.1830150313
|View full text |Cite
|
Sign up to set email alerts
|

T helper cell recognition of idiotopes on λ2 light chains of M315 and T952: evidence for dependence on somatic mutations in the third hypervariable region

Abstract: Previous work has indicated that BALB/c T helper cells (Th) recognize an idiotope expressed on a 88-114/117 fragment of V lambda 2 of BALB/c myeloma protein 315. In the present study the antigenic structure of this idiotope was further analyzed. Conventional carrier-specific Th elicited by immunization of BALB/c mice with free lambda 2(315) did not cross-react with the free lambda 2 chain of the BALB/c myeloma protein T952 which differs from lambda 2(315) in five amino acid positions (38, 94, 95, 96, 99). Simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…The diversity arises from both germline sequences and two fundamentally distinct somatic processes that occur at different points in B cell development. Results of previous studies have indicated that normal mice attain a state of tolerance to germline-encoded Ab diversity (25,26,32,33). In this study, we tested whether lupus-prone SNF 1 mice exhibit a global deficiency in such tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diversity arises from both germline sequences and two fundamentally distinct somatic processes that occur at different points in B cell development. Results of previous studies have indicated that normal mice attain a state of tolerance to germline-encoded Ab diversity (25,26,32,33). In this study, we tested whether lupus-prone SNF 1 mice exhibit a global deficiency in such tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, peptides from the BCR V region may provide an avenue of T cell help to autoreactive B cells. The BCR V region is promising in this regard because of the enormous diversity encompassed by V region peptides and because such peptides can be self-presented in class II MHC by activated B cells, which presumably are dependent upon T cell help (25)(26)(27)(28)(29)(30)(31)(32)(33)(34). We refer to this potential avenue of help to autoreactive B cells as the receptor presentation hypothesis (35).…”
Section: T Cell Tolerance To Germline-encoded Antibody Sequences In Amentioning
confidence: 99%
See 1 more Smart Citation
“…Such processed forms of immunoglobulin would associate with class II molecules and the complexes could be recognized on the surface of B cells by MHC-restricted T cells. However, as emphasized earlier (7,8), there are several possible limitations: (i) some immunoglobulins might be resistant to processing (16); (ii) peptides resulting from processing might not associate with class II molecules; and (iii) T cells might be tolerant to peptides derived from germ-line-encoded immunoglobulin (29). If the latter point is correct, T cells may participate only in the regulation of somatically mutated B-cell clones.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is much stronger for CD4 + than for CD8 + Id-specific T cells. As for CD4 + T cells, results obtained in the k2 315 Ig L-chain model [5,34] and in an anti-p-azophenylarsonate model [35,36] cells in vivo [34] and cloned CD4 + T cells in vitro [5,36] exclusively focused on V-region sequences that expressed somatic mutations, while no CD4 + T cell responses to germline sequences were found. Mutations appeared to influence binding of Id-peptides to MHC class II molecules on APC [7,15,36] as well as the recognition by the Id-reactive TCR [37].…”
Section: T-cell Tolerance To Id-peptides: Experimental Evidencementioning
confidence: 99%